Direct observation of morphological evolution of a catalyst during carbon nanotube forest growth: new insights into growth and growth termination. Issue 4 (24th December 2015) - Jeong, Seojeong; Lee, Jaegeun; Kim, Hwan-Chul; Hwang, Jun Yeon; Ku, Bon-Cheol; Zakharov, Dmitri N.; Maruyama, Benji; Stach, Eric A.; Kim, Seung Min
Abstract : Lifted catalysts lead to the growth termination of CNT arrays. Abstract : In this study, we develop a new methodology for transmission electron microscopy (TEM) analysis that enables us to directly investigate the interface between carbon nanotube (CNT) arrays and the catalyst and support layers for CNT forest growth without any damage induced by a post-growth TEM sample preparation. Using this methodology, we perform in situ and ex situ TEM investigations on the evolution of the morphology of the catalyst particles and observe the catalyst particles to climb up through CNT arrays during CNT forest growth. We speculate that the lifted catalysts significantly affect the growth and growth termination of CNT forests along with Ostwald ripening and sub-surface diffusion. Thus, we propose a modified growth termination model which better explains various phenomena related to the growth and growth termination of CNT forests.